Papillary endothelial hyperplasia in a TEC coronary atherectomy specimen. Issue 6 (June 1997) - Crilley, J. G.; Ritchie, C.; de Belder, M. A.
Abstract : Angiography in a 37 year old female with a three week history of typical crescendo angina found an 80% stenosis of the proximal left anterior descending (LAD) artery. The patient underwent percutaneous transluminal coronary angioplasty involving TEC artherectomy of the LAD artery. The specimen removed by atherectomy was found to have the appearance of papillary endothelial hyperplasia. This is an unusual histological diagnosis that occurs in association with thrombus. It is rarely found within arterial vessels and has not been reported in a coronary artery. Papillary endothelial hyperplasia is now thought to be a form of organising thrombus, probably dependent on the production of basic fibroblast growth factor by the endothelium.